Information and access to Public Higher Education by excluded citizens - Ribeiro, Marcela Arantes [UNESP]; Valentim, Marta Ligia Pomim [UNESP]; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Santa Catarina, 2022)
Objective: It addresses the importance of information for access to higher education in federal public institutions for historically excluded citizens, as an essential human action that aims to alleviate social inequalities and re-signify the social role of these institutions. Methods: With regard to methodological procedures, the research is qualitative in nature, of a bibliographic and documentary type, more specifically with regard to the address of Law 12.711, of August 29, 2012, which provides for admission to federal universities and federal institutions of secondary technical education and other measures. Results: The results reveal that information is an absolutely fundamental element access for these excluded citizens, as well as to awaken an understanding of the importance of educations in higher education for all. Conclusions: Multiple ways of discussing information were identified. In this research, the perspective of action was highlighted, which allows the user to appropriate certain information, leading him to understand the student selection process and the choice of any course. of graduation, in federal educational institutions, which will enable your social ascension and professional performance.
Keywords: Information; Appropriation of Information; Access to Public Higher Education; Excluded Citizens; Brazil